An emerging role for Cullin-3 mediated ubiquitination in sleep and circadian rhythm: Insights from Drosophila - Freeman, Amanda A.H. (Landes Bioscience, 2013)
Although the neurophysiological correlates of sleep have been thoroughly described, genetic mechanisms that control sleep architecture, long surmised from ethological studies, family histories and clinical observations, have only been investigated during the past decade. Key contributions to the molecular understanding of sleep have come from studies in Drosophila, benefitting from a strong history of circadian rhythm research. For instance, a number of recent papers have highlighted the role of the E3 ubiquitin ligase Cullin-3 in the regulation of circadian rhythm and sleep. We propose that different Cullin-3 substrate adaptors may affect specific molecular pathways and diverse aspects of circadian rhythm and sleep. We have previously shown that mutations in BTBD9, a risk factor for Restless Legs Syndrome (RLS) encoding a Cullin-3 substrate adaptor, lead to reduced dopamine, increased locomotion and sleep fragmentation. Here, we propose that Cullin-3 acts together with BTBD9 to limit the accumulation of iron regulatory proteins in conditions of iron deficiency. Our model is consistent with clinical observations implicating iron homeostasis in the pathophysiology of RLS and predicts that lack of BTBD9 leads to misregulation of cellular iron storage, inactivating the critical biosynthetic enzyme Tyrosine Hydroxylase in dopaminergic neurons, with consequent phenotypic effects on sleep.